High-dose-rate interstitial brachytherapy in early stage oral tongue cancer – 15 year experience from a tertiary care institute - Bansal, Anshuma; Ghoshal, Sushmita; Oinam, Arun S; Sharma, Suresh Chander; Dhanireddy, Bhaswanth; Kapoor, Rakesh (Journal of Contemporary Brachytherapy, 2016)
Purpose: To determine outcomes of interstitial high-dose-rate brachytherapy (HDR-BT) in patients with early stage oral tongue cancer. Material and methods : Ninety-two patients with stage I and II oral tongue cancer were treated with HDR-BT between 1999 and 2014: brachytherapy alone = 62 (67.4%), and combination of external beam radiotherapy (EBRT) and brachytherapy = 30 (32.6%). Median follow-up was 53.5 months. Patterns of failure, overall survival (OS), disease-free survival (DFS), local control rates (LCR), and nodal control rates (NCR) were determined. Results : 5-year OS, DFS, LCR, and NCR were 73.2%, 58.2%, 64.2%, and 83.8%, respectively. In total, 43 patients (46.7%) failed treatment: isolated local failures = 28 (30.4%), isolated nodal failures = 8 (8.7%), both local and regional failures = 7 (7.6%). While in T1 stage, 5 year LCR were significantly higher in brachytherapy alone group compared to combined EBRT and brachytherapy group (81.7% vs. 62.5%, p = 0.04), the isolated nodal failure rates were not significantly different among the two groups. For T2 stage, NCR were higher in combined EBRT and brachytherapy group compared to brachytherapy alone (92.9% vs. 74.3%). Acute mucositis (grade ≥ 2) was seen more in brachytherapy alone group compared to the combined modality group (87% vs. 66%), and this correlated significantly with the higher biological equivalent dose (BED) in the brachytherapy alone group. Conclusions : Our study recommends treating patients with brachytherapy alone in T1 stage, and demonstrates the need for addressing nodal region either by neck dissection or nodal irradiation in T2 stage patients. Also, the study highlights the need for dose escalation (from the doses used in the study) in both T1 and T2 stage tumors when using interstitial brachytherapy either as sole modality or as a boost.